Disfungsi Autonom pada Pasien Penyakit Jantung Hipertensi Asimptomatik: Hasil evaluasi pemulihan laju jantung - Yasmin Tadjoedin; Ismoyo Suni; Basuni Radi (Jurnal Kardiologi Indonesia, 2008)
Background.Imbalance of the autonomic nervous system has been known to have an important role in the pathophysiology of chronic heart failure (CHF). How early this imbalance occurs in CHF patients has not much been studied. We hypothesized that imbalance of the autonomic function evaluated with heart rate recovery (HRR) already occur in asymptomatic hypertensive patients with left ventricular hypertrophy (LVH) as subset of an early stage of CHF patients . Methods.Sixty two hypertensive patients (31 with LVH by echocardio-graphic criteria and 31 patients without LVH ) underwent treadmill exercise testing using the Bruce protocol and immediate supine on the recovery phase. Heart rate recovery was evaluated on minute 1 and 2 of the recov-ery phase and considered abnormal if = 18x/min in minute-1(HRR1) and = 42x/min in minute-2 (HRR2).Results.The mean HRR was significantly lower in hypertensive patients with LVH then the ones without LVH (19,48 ± 7,21 vs 26,45 ± 8,03) in minute-1, and (38,35 ± 11,19 vs 45,35 ± 9,97) in minute-2. An abnormal-ity in HRR1 percentage was found in 48.4% in patients with HHD and in 12.9% in patients without HHD. An inverse weak correlation (r = 0.329, p = 0.009) was found between LV mass index and HRR1.Conclusions.Abnormality of the HRR has already been found in hyper-tensive patients with LVH without signs or symptom of CHF suggesting an early occurrence of imbalance of the autonomic nervous system in early stage of CHF.